Indonesia's Youth Strategy Towards Sustainable Agricultural Change - Oktaviani, AuthNur Rizky; Rozaki, Zuhud; Wulandari, Retno; Distrianada, Ridho Ikbar (Universitas Muhammadiyah Yogyakarta, 2024)
Education and training focused on sustainable agriculture have a crucial role to play in preparing young Indonesians to play a role in sustainable agricultural change. This article discusses several internal and external factors influencing youth interest in the agricultural sector, including limited land constraints, inadequate financial support, negative views of agriculture, and the attractiveness of the non-agricultural sector in urban areas. Research shows that effective, practical, and up-to-date education and training programs can inspire youth to engage in sustainable agricultural practices. The importance of reviving youth interest in agriculture is also emphasized through the development of young entrepreneurs in the agricultural sector. Concrete measures such as increased access to technology, agricultural infrastructure development, and cooperation between governments, research institutions, and communities were identified as strategies to achieve sustainable agriculture. The importance of reviving youth interest in agriculture is also emphasized through the development of young entrepreneurs in the agricultural sector. Concrete measures such as increased access to technology, agricultural infrastructure development, and cooperation between governments, research institutions, and communities were identified as strategies to achieve sustainable agriculture. The importance of active youth participation in the policy process and cooperation with various parties was also discussed. Various training initiatives, such as the Kostratani Program at the Jambi Agricultural Training Center and thematic training activities for farmers, show the government's real commitment in increasing the capacity of agricultural human resources. However, challenges such as the labor crisis in the agricultural sector, especially among young farmers, have an impact on the aging of farmers. Strategies for the protection and empowerment of farmers according to Law Number 19 of 2013, which involve increasing resilience to climate change, business risk management, and strengthening market systems, were identified as steps that can be taken to address various problems in the agricultural sector.